Distribution and classification of soils - Rodriguez, Dario Martin; Schulz, Guillermo; Aleksa, Alicia Silvia; Tenti Vuegen, Leonardo Mauricio (Springer, 2024)
The systematic survey of the soils in Argentina began in the 1960s, led by the National Institute of Agricultural Technology (INTA). The US Soil Taxonomy was adopted as the soil classification system from the beginning of the Soil map of the Pampean Region Project in 1964. This chapter gives a comprehensive overview of the Argentine soils on the basis of the cartographic and descriptive information of the Argentine Soil Atlas, gathered by soil experts of the institution. The overview comprises a brief description of the main characteristics and geographical location of the 12 soil orders and their suborders that were identified along the diverse landscapes found in the vast geography of the country. Mollisols, Entisols, and Aridisols are the most conspicuous soil orders since they cover almost two-thirds of the country.